2018
DOI: 10.11648/j.sjc.20180604.15
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State of <sup>229</sup>Th Recoils Implanted into MgF<sub>2</sub> Crystals

Abstract: A solid-state nuclear clock based on the low-lying isomeric state in 229 Th has attracted growing interest. One potential problem for the solid-state nuclear clock approach is the suitability of the doped environment for photon emission of the nuclear isomeric state. Specifically, Th n+ n < 4 ions could open non-radiative decay routes for deexcitation, hindering the photon emission. Here we have used time-resolved photoluminescence (TRPL) and density functional theory (DFT) calculations to characterize MgF 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…To achieve convergence, SCAN requires a much larger energy cutoff in contrast to LDA, where it was possible to use only 400 eV. In agreement with Barker et al [43], we report that the most favorable configuration is the Mg-vacancy and our calculations also show, that the +2F interstitial charge compensation has almost no energy preference for a linear or bent structure. However, the energy difference between the Mg-vacancy and the +2F configuration is 2.7 eV in our results and thus slightly larger than in the previous study, which reported 2.5 eV.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…To achieve convergence, SCAN requires a much larger energy cutoff in contrast to LDA, where it was possible to use only 400 eV. In agreement with Barker et al [43], we report that the most favorable configuration is the Mg-vacancy and our calculations also show, that the +2F interstitial charge compensation has almost no energy preference for a linear or bent structure. However, the energy difference between the Mg-vacancy and the +2F configuration is 2.7 eV in our results and thus slightly larger than in the previous study, which reported 2.5 eV.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Barker et al [43] performed DFT calculations for thorium-doped MgF 2 . In this work, the preferred charge compensating mechanism was also determined to be the Mgvacancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral filters can be used to obtain information about the emitted photon energies. Experiments along this line were carried out since 2007 at various institutes around the world [9,53,192,343,413,419,422], however with negative results. A direct detection of the isomeric decay by this method was reported in 2012 [419].…”
Section: Population Via a Natural Decay Branchmentioning
confidence: 99%
“…These crystals are expected to also provide the basis for solid-state nuclear frequency standards [179]. Significant progress has been made in crystal development and theoretical understanding [9,79,85,107,127,150,178,262,287,316,335,337]. Two experimental results using synchrotron radiation have been reported, which were, however, negative: the first one performed by UCLA, using the Advanced Light Source (ALS) of the Lawrence Berkeley National Laboratory [151,152] the second one performed by the Technical University of Vienna, using the Metrology Light Source (MLS) in Berlin, Germany [338].…”
Section: Population Via Direct Excitationmentioning
confidence: 99%